Trabalho análogo à escravidão : reconhecimento e fundamentalidade - Figueiredo, Vanessa Rosin (2021)
This dissertation analyzes the occurrence of the phenomenon of contemporary slavery since its emergence with the extinction of colonial slavery, the economic and social factors that influenced its emergence, as well as its permanence to the present days. In addition, it examines the jurisprudential interpretations about the characterization of slave-like work and its contemporary forms. Freedom and the ability to self-determine, as an essential quantity to the human being, are inserted due to its relevance and pertinence to work, considerations about subordination as a boundary of the worker's autonomy are done. Work is considered by its value as a fundamental right, as an intrinsic element of the human existence and as an instrument of recognition, achievement and social esteem. Human dignity as the apex of the Brazilian legal system is pondered by its scope and extension, besides being the basis of the constitutional objectivist theory for the repair of extrapatrimonial damages. It aims, with the aid of the deductive method, to ascertain the elements of the contemporary theory of extra-patrimonial damages, moral and existential damage in the light of the CLT and the Civil Code, advancing the discussion on the presumption of damages in the face of the verified violation of human dignity and fundamental rights, just as to investigate the application of the reversal of the evidentiary burden based on the dynamic burden of proof theory and the protective principle. We conclude that there is a need for the effective application of the protective principle, of human dignity, in order to obtain a fair and equitable process that provides just reparations for victims of labor analogous to slavery.